PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN (STUDI PADA KONSUMEN PRODUK BODY SPLASH MUSTIKA RATU SWALAYAN ADA SETIABUDI) - Hasna, Adibah; Hidayat, Wahyu; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Cosmetics variety are not only seen as a mere fulfillment. From the other side, consumers are also diverse female cosmetics users. In reality, cosmetics company facing a very heterogeneous market. A concern that the manufacturer does not know who the target market companies, actually, given the female consumer is very large cosmetics users or almost all women use cosmetics, cosmetics outstanding variety can also be interpreted as an implementation of the intense competition among cosmetics industry. The problems in this study is the decline in customer loyalty products Body Splash Mustika Ratu ADA Setiabudi Semarang which indicated a decrease in the purchase of products by customers loyal. Based prasurvey conducted by researchers of the customer product Body Splash Mustika Ratu ADA Setiabudi Semarang, most customers products Body Splash Mustika Ratu feel dissatisfied with customer products Mustika Ratu Body Splash. Customer dissatisfaction is allegedly caused by factors brand image and product quality.This study was conducted to determine the effect of brand image and product quality to customer satisfaction and loyalty products Body Splash Mustika Ratu. In this research using random sampling technique respondent sampling, the number of respondents of 100 respondents. Analysis of the data used is path analysis.The results showed that the image of the brand and quality of products both partially and simultaneously a positive effect on customer satisfaction and loyalty. Based on the results of the calculation of the variable path analysis showed that customer satisfaction is a mediating variable to variable customer loyalty. Advice for companies is because there are respondents who feel that the product Body Splash Mustika Ratu less prestigious. Mustika Ratu should try to improve consumers' perceptions of products Mustika Ratu Body Splash for creating the perception that using the product Mustika Ratu Body Splash is a pride. Mustika Ratu should add to the features of the product Body Splash with the aim to increase the benefits and usefulness of Body Splash Mustika Ratu products for consumers.